2018
DOI: 10.1071/bt17116
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental parameters show associations with essential oil composition in West Australian sandalwood (Santalum spicatum)

Abstract: Santalum spicatum (R.Br.) A.DC is a West Australian sandalwood species highly valued for the sesquiterpene-rich oil in mature heartwood. The oil composition, particularly levels of the valuable sesquiterpenoids α- and β-santalol and the allergenic E,E-farnesol, are known to vary across its natural distribution. Our study investigated associations of oil characteristics in 186 S. spicatum trees in semiarid and arid regions of Western Australia with genetic structure, environmental parameters and morphological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Te phytochemical composition of genus Osyris includes volatile constituents that are important in essential oils and are known as sesquiterpenes. Te superiority of sandalwood oil is determined by the level of alpha (α) and beta (β) santalol relative to the international oil quality standards for these compounds [27]. Te GC-MS analysis in this study recognized compounds belonging to groups of hydrocarbons, fatty acids, esters, alcohols, amines, sesquiterpenes, among others, in Osyris oil.…”
Section: Oil Quality Potential In Diferent Provenances In Kenyamentioning
confidence: 89%
“…Te phytochemical composition of genus Osyris includes volatile constituents that are important in essential oils and are known as sesquiterpenes. Te superiority of sandalwood oil is determined by the level of alpha (α) and beta (β) santalol relative to the international oil quality standards for these compounds [27]. Te GC-MS analysis in this study recognized compounds belonging to groups of hydrocarbons, fatty acids, esters, alcohols, amines, sesquiterpenes, among others, in Osyris oil.…”
Section: Oil Quality Potential In Diferent Provenances In Kenyamentioning
confidence: 89%
“…In the present study, we found that the oil composition and genetic structure by the genic markers were not significantly correlated in S. album (Table 6). Likewise, the association of genetic structure as well as oil composition in S. spicatum was independent variables and determined by environmental factors mainly on geographical regions (soil-type factor) of the populations (Moniodis et al 2018). In this study, we found that the pattern of sandalwood oil component variation (α-santalol, trans-β-santalol, E-cis-epi-β bergamotol, and trans Z-α santalol) was significantly associated with environmental factors, which might affect the genetic structure variability.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, global sandalwood resources have diminished since 1980, and demand is high [ 5 ]. In the long run, expanding plantations could alleviate the need to harvest natural populations but stringent conservation efforts are needed to thwart the decline of natural resources [ 6 ]. Enhancement of heartwood formation, especially through increasing plantation productivity, is an important means for creating sustainable sandalwood resources.…”
Section: Introductionmentioning
confidence: 99%